KONTRIBUSI KEPALA SEKOLAH DALAM PENGEMBANGAN PROFESIONALITAS TENAGA PENDIDIK DI MADRASAH ALIYAH PONDOK PESANTREN DARUSSALAM SUBANG, JAWA BARAT - Monica Ekza Pramudya; Acep Nurlaeli (Universitas Islam Lamongan, 2022)
The principal's leadership style can influence one professional teacher's performance. This research aims to determine the performance of school principals in improving the professionalism of education personnel, along with their leadership styles and managerial abilities. This study uses descriptive qualitative, observation data collection techniques, documentation studies, and interviews with the research subjects, the principal, and the teacher council. The study results indicate that the principal's policy program in improving teacher performance begins with equalizing the perception and vision of the principal with his staff and senior teachers. In addition, schools as leaders do many empowering teachers according to the ability and willingness of teachers, establishing cooperation, completing infrastructure, and encouraging teachers to be active in Teacher Working Groups (KKG). The principal's leadership style in fostering and guiding teachers is instructive, consultative, participatory, and delegative in directing and influencing teachers to achieve educational goals.